O lugar da especulação na elaboração das hipóteses metapsicológicas de além do princípio de prazer - Albuquerque, Alice Vieira de (2018)
In order to understand the speculative method used by Freud to elaborate the metapsychological concepts, this study uses as a strategy following the construction of the metapsychological hypothesis developed by the author in the article Beyond the Pleasure Principle (1920). The study intends to show how the explanations based mainly on the biological model of the psyche lead to the sequence of speculative hypothesis that lead to the central (and quite controversial) concept of the 1920’s article, which caused a considerable turnaround in psychoanalytical theory – the death drive. For this purpose, we compared the schemes of psychic apparatus developed by Freud in 1895 and 1900 to the one exposed in Beyond..., emphasizing the difference between the psyche conceived through the mechanical and the biological models. In the abovementioned works, it is possible to verify that the author uses the mechanical model of explanation, referring to the flow of quantities, or the difference between rest and movement, conveyed from one to the other element in the psychic apparatus. The use of the biological model of explanation concerns to the evolution and the development of the elements that make up the system, responsible for the refinement of its performance, aiming at adaptation. In Beyond the Pleasure Principle (1920), the biological model of explanation has a major role, occasion in which the psyche is conceived from an evolutive perspective, since its origin and the assertions that are openly described as speculative constitute a crucial axis upon which the text is formulated. It is in this scenario that the drive’s finality ‒ the absolute discharge of energy or the return to the inorganic ‒ is expressly articulated.